Thrombogenesis of the Rabbit Arterial Plaque: An Electron Microscopic Study - Stemerman, Michael B. (1973)
Rabbit arteries, de-endothelialized with an intravascular balloon catheter and allowed to heal for 4 weeks, showed intimal changes that were similar to the preatherosclerotic fibromusculoelastic plaques of man. Reinjury of the healed vessels by balloon catheter produced marked quantitative and qualitative alterations of hemostasis, as compared to that in previously uninjured vessels. The most apparent modification of thrombogenesis 10 minutes after injury to the plaque was a large increase in the size of the thrombotic deposits. Features of this exaggerated response were the major participation of fibrin in thrombus formation and greater platelet accumulation. Some platelets and fibrin strands appeared to penetrate into and beneath the neointima. By 3 hours, these deposits had diminished in size, although the hemostatic mass remained larger in the doubly injured vessels.